PREPARATION AND RECOVERY OF IRON CARBIDE FROM PYRITE CINDER VIA A CARBURIZATION-MAGNETIC SEPARATION TECHNOLOGY - Dong Chen; Hongwei Guo; Yanan Lv; Peng Li; Bingji Yan; Jifang Xu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
A new technique with carburization followed by magnetic separation is presented for the preparation of high-grade iron carbide from pyrite cinder to promote the high value-added utilization of pyrite cinder. The effects of carburizing temperature, carburizing time, Na2SO4 dosage and grinding fineness were investigated. The optimized process parameters were proposed as the following: carburizing at 650 °C for 180 minutes in CO-CO2-H2 gas mixtures, Na2SO4 dosage of 9%, grinding to a particle size of 92.25% less than 0.025mm, and magnetic field intensity of 130 mT. Under the optimized conditions, the iron content, total carbon content, total iron and carbon content of magnetic concentrate were 82.62%, 5.60%, and 88.22%, respectively. The iron recovery rate was 88.67%. Furthermore, the carburization behavior, separation mechanism and Na2SO4 function were ascertained with optical microscopy, X-ray powder diffraction and scanning electron microscope.